Plasma Transport in Saturn's Low‐Latitude Ionosphere: Cassini Data. Issue 6 (29th June 2019) - Cravens, T. E.; Morooka, M.; Renzaglia, A.; Moore, L.; Waite, J. H.; Perryman, R.; Perry, M.; Wahlund, J.‐E.; Persoon, A.; Hadid, L.
Abstract: In 2017 the Cassini Orbiter made the first in situ measurements of the upper atmosphere and ionosphere of Saturn. The Ion and Neutral Mass Spectrometer in its ion mode measured densities of light ion species (H +, H2 +, H3 +, and He + ), and the Radio and Plasma Wave Science instrument measured electron densities. During proximal orbit 287 (denoted P287), Cassini reached down to an altitude of about 3, 000 km above the 1 bar atmospheric pressure level. The topside ionosphere plasma densities measured for P287 were consistent with ionospheric measurements during other proximal orbits. Spacecraft potentials were measured by the Radio and Plasma Wave Science Langmuir probe and are typically about negative 0.3 V. Also, for this one orbit, Ion and Neutral Mass Spectrometer was operated in an instrument mode allowing the energies of incident H + ions to be measured. H + is the major ion species in the topside ionosphere. Ion flow speeds relative to Saturn's atmosphere were determined. In the southern hemisphere, including near closest approach, the measured ion speeds were close to zero relative to Saturn's corotating atmosphere, but for northern latitudes, southward ion flow of about 3 km/s was observed. One possible interpretation is that the ring shadowing of the southern hemisphere sets up an interhemispheric plasma pressure gradient driving this flow. Key Points: First in situ ion flow measurements in an outer planet ionosphere are shown Protons dominate Saturn's equatorial topside ionosphere, and Cassini data showed that they flow from the Northern to the southern hemisphere The Cassini Ion and Neutral Mass Spectrometer measured proton flow speeds in Saturn's ionosphere as high as 3 km/s